Selecting and Applying "Defense Strategy" of PT. Infomedia Nusantara - Cahyaningtyas, RR Febie; Toha, Mohammad (The Indonesian Journal of Business Administration, 2014)
Abstract â€“ PT. Infomedia Nusantara is Indonesia based company in service industry that has two cores business: contact center and business process management. Currently, the competitor is about to attack the company in the present segment, which is Enterprise Shared Service. The right defense strategy is needed in order to defend the competitor and to sustain the growth. The objective of the final project is to know what key success factors and what suitable defense strategy for PT. Infomedia Nusantara. Business exploration is done by define internal and external analysis. Internal analysis tool that is used is value chain analysis, while external analysis tools that is used are PEST analysis and Porterâ€™s five forces. SWOT analysis is determined from both of internal and external analysis. Strategy is formulated by conducting a simple qualitative method market research in order to get the key success factors. The results of interviewed 13 customers from different industry segment are nine key success factors. Company and competitor characteristics are also determined to know the strength and weakness of both. The result is PT. Infomedia Nusantara uses differentiation strategy. The suitable defense strategy for the company is â€œholding the groundâ€ defense strategy, which means the company have to perform several tactics to defend competitor along with maximize the strengths and minimize the weaknesses. Five tactics are made based on the key success factors; (1) improve the quality (2) training in regular basis (3) increase good reputation (4) provide LO for different type of customers (5) strengthen the synergy with Telkom group.Â Keywords: strategic business, defense strategy, key success factors, business process management